1986
DOI: 10.1007/bf00446361
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of a nitrogen-fixing cyanobacterium into tobacco shoot regenerates

Abstract: Tobacco (Nicotiana tabacum L.) shoots associated with the nitrogen-fixing cyanobacterium Anabaena variabilis Kütz. (ATCC 29413) were regenerated in mixed cultures of tobacco callus and the cyanobacterium. The cyanobacteria were localized inside the tissues as well as on the surface of regenerated shoots, formed heterocysts, and were capable of acetylene reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…The extension of the range of plants with the ability to fix nitrogen has been a long-term objective of plant scientists, which can have great environmental and economic significance. In this context, cyanobacteria are particularly suitable for the creation of novel nitrogen-fixing associations since they already form a wide variety of natural symbiotic associations (Gusev et al 1986;Rai 1990;Rai et al 2000). Nilsson et al (2002Nilsson et al ( , 2005Nilsson et al ( , 2006 tested numerous symbiotic cyanobacterial isolates for their ability to associate with rice and demonstrated that symbiotically competent Nostoc strains respond chemotactically to extracts of natural host and non-host plants.…”
Section: Resultsmentioning
confidence: 98%
“…The extension of the range of plants with the ability to fix nitrogen has been a long-term objective of plant scientists, which can have great environmental and economic significance. In this context, cyanobacteria are particularly suitable for the creation of novel nitrogen-fixing associations since they already form a wide variety of natural symbiotic associations (Gusev et al 1986;Rai 1990;Rai et al 2000). Nilsson et al (2002Nilsson et al ( , 2005Nilsson et al ( , 2006 tested numerous symbiotic cyanobacterial isolates for their ability to associate with rice and demonstrated that symbiotically competent Nostoc strains respond chemotactically to extracts of natural host and non-host plants.…”
Section: Resultsmentioning
confidence: 98%
“…Cyanobacteria have been mixed with Daucus cells (Bradley, 1980), but there was no successful regeneration. Gusev et al (1986) were able to regenerate tobacco shoots, which contained cyanobacteria in their intercellular spaces, but they did not root the regenerates. Azospirilla have also been cultured together with plant tissues.…”
Section: Introductionmentioning
confidence: 95%
“…The creation of novel symbioses with Ngfixing microorganisms may provide an alternative method to the introduction of isolated nif genes into plants. To date, novel associations between Rhizobium and rice (Al-Mallah, Davey & Cocking, 1989) and between Anabaena and tobacco (Gusev et al, 1986) have been reported. The former association was obtained by treating rice roots with cell wall degrading enzymes followed by inoculation with rhizobia.…”
Section: Introductionmentioning
confidence: 99%